The Architecture of Disagreement: A Philosophical Inquiry into Identity, Public Reason, and Secularism in Plural Democracies - Sirajun Nasihin; Arfi Hidayat (UIN Sunan Kalijaga Yogyakarta, 2025)
Contemporary democratic theory has produced three largely separate lines of inquiry: institutional design for managing identity conflict, norms of public discourse in plural societies, and models of state–religion relations. This article argues that their analytical separation is not merely a thematic division of labor but a philosophical deficiency each framework generates normative requirements it cannot fulfill without presupposing what the other two provide. That interdependency is the article's central claim, and its demonstration constitutes the article's primary contribution. Using philosophical reconstruction and internal normative critique as its method, this article addresses three interconnected problems: how identity claims can receive recognition without negating democratic equality; whether democratic stability requires substantive consensus or can rest on shared procedures of public justification; and whether secularism is a normative prerequisite for democracy or a contestable constitutional commitment subject to ongoing democratic revision. Through critical engagement with Rawls's political liberalism, Mouffe's agonistic pluralism, An-Na'im's civic reason, Stepan's twin tolerations, and Bhargava's principled distance, the article constructs an integrated three-dimensional framework that treats managed dissensus rather than final consensus as the constitutive condition of democratic legitimacy under deep pluralism. The article's core argument is that identity recognition becomes democratically legitimate not when it achieves resolution, but when it operates within publicly accountable limits: conditions under which disagreement is still conducted among civic equals rather than deployed as a strategy for dismantling equality itself. Plural democracy is not sustained by eliminating conflict but by institutionally distinguishing productive dissensus from antagonism that destroys the very terms of democratic coexistence.